The Effectiveness of Dates and Beets on Hemoglobin Levels in Trimester II Pregnant Women at BPM Titin Sumarni - Titin Sumarni; Nanik Yuliwati (International Journal of Medicine and Health, 2023)
Backgrounds : Low hemoglobin levels often occur in pregnant women, low hemoglobin levels are a serious problem for pregnant women because the lack of hemoglobin levels will have a negative impact during the delivery process. Research Objectives: To determine the effectiveness of dates and beets on Hemoglobin levels in second trimester pregnant women at TPMB Titin Sumarni, Babelan Village, Babelan District, Bekasi Regency. Research Methods : This study used a quasi-experimental with purposive sampling with a sample of 32 people. Data techniques included in uivariate analysis using frequency distribution and bivariate analysis using statistical calculations The results of the study : Respondents in the control group and the intervention group mostly worked as housewives, in the intervention group there was an increase in hemoglobin levels in the second trimester of pregnant women, thus proving the effectiveness of giving beets and dates to increase hemoglobin levels in the second trimester pregnant women. Conclusions and suggestions : Conclusions From the results of this study it was found that there was effectiveness in giving beets and dates to increase hemoglobin levels in the second trimester of pregnant women at BPM Titin Sumarni. Suggestions for providing information about good nutrition for pregnant women by providing health promotion and education to visiting pregnant women to reduce mortality and morbidity due to anemia.